Oxidative radical-mediated addition of ethers to quinone imine ketals: an access to hemiaminals - More, Satish G.; Kamble, Rohit B.; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2021)
The highly regioselective synthesis of substituted hemiaminal via addition of ethers to quinone imine ketals (QIKs) has been developed under metal-free conditions. In the presence of tetrabutylammonium chloride and potassium persulfate (K2S2O8), QIKs couple efficiently with cyclic and acyclic ethers to give hemiaminals. This strategy offers an easy access to substituted hemiaminal ethers with high functional group tolerance in good to excellent yields.